Laboratory testing on cracking characteristics and improvement mechanism of coral mud - Huaqiang Fang; Xuanming Ding; Yifu Li; Hong Wang; Junyu Ren (Biogeotechnics)
In recent years, the development and construction of island reefs have been flourishing. Due to the remoteness of island reefs from the mainland, the scarcity of building materials, and the high transportation costs, it is imperative to use local marine resources, and the potential value and status of coral mud on island reefs, which is formed by the remains of corals and other biological entities, is becoming increasingly prominent. Utilization and optimization of natural resources on island reefs have become a brand-new research direction and challenge. This article mainly focuses on the development of a new type of green engineering material, coral mud, for use in building surface layers. Thickness effects, PVA fiber (vinylon staple fiber) modification, and HPMC (Hydroxypropyl Methyl Cellulose) adhesive modification are taken into consideration. Through laboratory tests and image processing technology, fractal theory, and electron microscopy experiments, the macro-meso-microscopic multi-scale cracking rules of the coral mud surface layer and the optimization modification rules of PVA fibers and HPMC adhesives are revealed. The results demonstrate that the performance of the coral mud surface layer is superior to that of the kaolin surface layer, and the 10 mm thickness performs better than the 5 mm and 20 mm thicknesses. As the thickness of the coral mud surface layer increases, the contact between coral mud particles becomes denser, the scale of surface micro-cracks decreases, and the number of micro-pores decreases. PVA fibers can effectively inhibit the further development of macro and micro cracks and play a good bridging role. There is a bonding and adhesion relationship between coral mud and PVA fibers, and they have a good synergistic effect in inhibiting macro and mesoscopic cracks. With the increase in HPMC adhesive content, the number of micro-cracks and the scale of micro-cracks decrease accordingly, and the structure and performance of the coral mud surface layer are further improved. Overall, PVA fibers are more effective than HPMC adhesives in inhibiting the cracking of the coral mud surface layer. This provides valuable guidance for the development and application of coral mud in wall surface materials.